A low-frequency rotational electromagnetic energy harvester using a magnetic plucking mechanism. (1st January 2022) - Miao, Gang; Fang, Shitong; Wang, Suo; Zhou, Shengxi
Highlights: A novel rotational electromagnetic plucking energy harvester is proposed. The resetting effect is used to improve energy harvesting performance. The influence mechanism of the resetting effect is revealed. The maximum average output power reaches 13.13 mW in experiment. Abstract: Energy harvesting from rotational motion, such as vehicle tires and rotational devices, remains a challenge because of the difficulty of balancing the harvesting frequency range and the power-generation density and efficiency. Traditional energy harvesters using the mechanism of magnetic plucking and piezoelectric conversion cannot overcome the inherent disadvantages of the output power and the strictness of the application conditions. In this study, a low-frequency rotational electromagnetic energy harvester using a nonlinear magnetic plucking configuration is proposed. Using the novel structure to pluck a cylindroid generating magnet in each rotational motion, the resetting effect provides a new way to stabilize the output voltage and improve the energy harvesting performance. Two design factors for controlling the resetting effect were studied theoretically and experimentally. The finite element method based on the Maxwell stress tensor not only helps in understanding the magnetic field density distribution in the energy harvesting process but also reveals the resetting mechanism. Simulating a vehicle tire with a diameter of 0.6 m rotating at a speed of approximately 20 km/h, it was experimentally validated that the maximum average output power across all the rotating frequencies (0.5–5.0 Hz) reached 13.13 mW under certain excitation conditions in the experiment, which is increased by 215.9% compared with the harvester without the resetting effect. The great performance under different application conditions demonstrated that the proposed electromagnetic energy harvester has a great potential in energy harvesting from low-frequency rotational motions.